Porphyrin-engineered nanoscale metal-organic frameworks: enhancing photodynamic therapy and ferroptosis in oncology - Zou, Yutao; Chen, Jiayi; Luo, Xuanxuan; Qu, Yijie; Zhou, Mengjiao; Xia, Rui; Wang, Weiqi; Zheng, Xiaohua (Frontiers in Pharmacology, 2024)
Photodynamic therapy and ferroptosis induction have risen as vanguard oncological interventions, distinguished by their precision and ability to target vulnerabilities in cancer cells. Photodynamic therapy's non-invasive profile and selective cytotoxicity complement ferroptosis' unique mode of action, which exploits iron-dependent lipid peroxidation, offering a pathway to overcome chemoresistance with lower systemic impact. The synergism between photodynamic therapy and ferroptosis is underscored by the depletion of glutathione and glutathione peroxidase 4 inhibitions by photodynamic therapy-induced reactive oxygen species, amplifying lipid peroxidation and enhancing ferroptotic cell death. This synergy presents an opportunity to refine cancer treatment by modulating redox homeostasis. Porphyrin-based nanoscale metalorganic frameworks have unique hybrid structures and exceptional properties. These frameworks can serve as a platform for integrating photodynamic therapy and ferroptosis through carefully designed structures and functions. These nanostructures can be engineered to deliver multiple therapeutic modalities simultaneously, marking a pivotal advance in multimodal cancer therapy. This review synthesizes recent progress in porphyrin-modified nanoscale metal-organic frameworks for combined photodynamic therapy and ferroptosis, delineating the mechanisms that underlie their synergistic effects in a multimodal context. It underscores the potential of porphyrinbased nanoscale metal-organic frameworks as advanced nanocarriers in oncology, propelling the field toward more efficacious and tailored cancer treatments.